RETRACTED: Methodological approach to solving the problem of increasing energy efficiency in residential buildings - Ovchinnikova Svetlana; Konstantinov Ivan; Radwan Hussein; Martynyuk Alexey; Nikolenko Vladislav (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001